2006
DOI: 10.1097/01.pgp.0000233168.41138.ae
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Serous Cystadenofibroma With Stromal Sex Cord Elements

Abstract: This report describes an ovarian serous cystadenofibroma, in a postmenopausal woman, which exhibited extensive sex cord differentiation, in the form of solid and hollow tubules resembling Sertoli cell elements, within the stroma. The sex cord elements, which were located just beneath the epithelium, were positive with both alpha inhibin and calretinin and negative with epithelial membrane antigen. They were also CD56 positive but negative with other neuroendocrine markers. True sex cord structures or sex cord-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Although we are not aware of any documented cases of glandular proliferations co-expressing CDX-2 and ER by immunohistochemistry arising in cystadenofibromatous background as we describe here, there are scattered case reports of other unusual proliferations in this setting. Dillon and colleagues reported a unique serous cystadenofibroma with stromal sex cord elements (7). As in our cases, the surface epithelium showed no borderline or malignant features.…”
Section: Discussionsupporting
confidence: 70%
“…Although we are not aware of any documented cases of glandular proliferations co-expressing CDX-2 and ER by immunohistochemistry arising in cystadenofibromatous background as we describe here, there are scattered case reports of other unusual proliferations in this setting. Dillon and colleagues reported a unique serous cystadenofibroma with stromal sex cord elements (7). As in our cases, the surface epithelium showed no borderline or malignant features.…”
Section: Discussionsupporting
confidence: 70%
“…That case may be similar to our case although a granulosa, as opposed to cellular theca component, is not convincingly documented. Another case has been reported of stromal sex cord elements resembling Sertoli tubules arising in the stroma of an ovarian serous cystadenofibroma (18). To our knowledge, composite granulosa cell tumor with other surface epithelial tumors has not been reported.…”
Section: Discussionmentioning
confidence: 86%
“…Dillon et al, reported in serous cyst adenofibroma with stromal sex cord elements whereas Ueda et al, reported in mucinous epithelial ovarian tumour with stromal sex cord elements. 16,17 Most of the tumours reported in literature are unilateral tumours except in one literature bilateral ovarian fibroma with minor sex cord elements are reported (Gupta et al). 18 Few cases in extraovarian site also reported as fibroma with minor sex cord elements in broad ligament (Omori et al).…”
Section: Discussionmentioning
confidence: 99%